Expression of tissue inhibitors of metalloproteinases type 1 and type 2 in the leaflets of explanted bioprosthetic heart valves: a new pathogenetic parallel between structural valve degeneration and calcific aortic stenosis - A. E. Kostyunin; T. V. Glushkova; L. A. Bogdanov; E. A. Ovcharenko (Вестник трансплантологии и искусственных органов)
Objective: to study cellular and lipid infiltration, as well as the expression of tissue inhibitors of metalloproteinases (TIMP) types 1 and 2 in biological prosthetic heart valves (BPHVs) explanted due to dysfunction.Material and Methods. We examined 17 leaflets from 6 BPHVs, dissected from the aortic and mitral positions during valve replacement. For microscopic analysis, fragments of the BPHV leaflets were frozen and serial sections were made using a cryotome. In order to study cellular infiltration and the degree of degenerative changes in the prosthetic biomaterial, the sections were stained with Gill’s hematoxylin and eosin; Oil Red O stain was used to assess lipid deposition. Immunohistochemistry was used for cell typing and detection of TIMP-1/-2. The stained samples were analyzed by light microscopy.Results. Cellular and lipid infiltration of xenogeneic tissues was detected in all BPHV flaps studied. Recipient cells coexpressed pan-leukocyte and macrophage markers PTPRC/CD45 and CD68. Positive staining for TIMP-1/-2 co-localized with cell clusters but was absent in acellular sections.Conclusion. Cells infiltrating xenogeneic BPHV tissues express TIMP-1/-2. This suggests that BPHV immune rejection pathophysiology is partially similar to that of calcific aortic stenosis.